Compassionate love and dispositional forgiveness: does compassionate love predict dispositional forgiveness? - Kim, Jichan J. (Journal of spirituality in mental health, 2022)
Despite the conceptual link between love and forgiveness, empirical evidence for the relationship between the two is scarce. Also, controversy exists surrounding the use of a self-evaluated forgiveness tendency as a measure of dispositional forgiveness. One hundred adults filled out an online survey to provide the data for this study. Compassionate love, commitment to forgiveness, and valuing forgiveness were moderately associated with dispositional forgiveness. Compassionate love predicted dispositional forgiveness over and above all other measures. The feasibility of measuring dispositional forgiveness accounting for the occurrences of actual transgressions and the presence of compassionate love among those showing forgivingness are discussed.